The use of digital applications in horse farm management in jeneponto regency - Nurul Magfirah Ashar; Andi Nur Syahbani (Fakultas Pertanian Universitas Majalengka, 2026)
Digital transformation in the livestock sector is one of the efforts to improve business management efficiency and expand market access for farmers. However, the utilization of digital technology in rural areas still faces various obstacles, particularly regarding infrastructure, digital literacy, and human resource readiness. This study aims to assess the level of digital application adoption among horse farmers and identify factors influencing its utilization in the management of horse farms in Tolo Timur Village, Kelara Subdistrict, Jeneponto Regency. This study employs a qualitative approach supported by descriptive quantitative data, with data collection techniques including interviews, questionnaires, observations, and a literature review, involving 30 horse farmers selected using simple random sampling. Data were analyzed descriptively using a Likert scale to measure farmers' perceptions regarding several indicators: internet availability, ease of application use, application utilization in livestock business management, and interest in participating in digital training. The results of the study indicate that only half of the farmers (50%) own a smartphone, and the utilization of digital applications in livestock business management remains relatively low. The main challenges include limited digital literacy, limited experience with technology, and the perception that digital applications remain difficult to use in livestock business activities. Nevertheless, some farmers expressed an interest in participating in training on the use of digital applications. Therefore, support is needed in the form of improved digital literacy, training and mentoring for farmers, and the development of simple, user-friendly applications to enable the optimal use of digital technology in the livestock sector.